EVALUATION OF BRAIN TUMORS USING MAGNETIC RESONANCE IMAGING IN ADULT PATIENTS - Khodjibekov M.Kh., Alisherova M.A., Ilhamov D.F., (Central Asian Journal of Medicine, 2025)
This descriptive and analytical study was carried out at the Republican Specialized Scientific-Practical Center of Neurosurgery between January 2023 and September 2023 to assess brain tumors using Magnetic Resonance Imaging (MRI). The study included a sample of 30 patients, both male and female, aged between 20 and 80 years, who were suspected of having brain tumors. The results indicated that the most affected age group was 40 to 60 years, accounting for 46.7% of cases, whereas the 60 to 80-year age group had the lowest prevalence at 16.7%. Female patients were more commonly affected than males, making up 53% of cases compared to 47% for males. Non-malignant tumors were the most prevalent, comprising 57% of cases. Among malignant tumors, 84.7% were classified as primary, while 15.3% were secondary. Meningioma was the most frequently observed tumor type on MRI, accounting for 43.3% of cases in both male and female patients.